Protocol for photo-controlling the assembly of cyclic peptide nanotubes in solution and inside microfluidic droplets - Marcos Vilela-Picos; Federica Novelli; Alejandro Méndez-Ardoy; Alessandro Moretto; Juan R. Granja (STAR Protocols, 2024)
Summary: In this protocol, we describe how to perform the photo-isomerization of cyclic peptides containing an unsaturated β-amino acid. This process triggers the formation or disassembly of cyclic peptide nanotubes under appropriate light irradiation. Specifically, we start by describing the solid-phase synthesis of the cyclic peptide component. We also present a technique for performing isomerization studies in solution and how to extend it to microfluidic aqueous droplets.For complete details on the use and execution of this protocol, please refer to Vilela-Picos et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.